2006
DOI: 10.1074/jbc.m607007200
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Triggers Autophagy

Abstract: Eukaryotic cells have evolved strategies to respond to stress conditions. For example, autophagy in yeast is primarily a response to the stress of nutrient limitation. Autophagy is a catabolic process for the degradation and recycling of cytosolic, long lived, or aggregated proteins and excess or defective organelles. In this study, we demonstrate a new pathway for the induction of autophagy. In the endoplasmic reticulum (ER), accumulation of misfolded proteins causes stress and activates the unfolded protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
736
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 897 publications
(758 citation statements)
references
References 43 publications
16
736
4
2
Order By: Relevance
“…Intriguingly, parallel to UPR induction hypericin-PDT induces Atgs ( Table 1), suggesting that this cellular degradation process may be initiated to reestablish ER homeostasis following photodamage. This is supported by recent studies pointing to ER stress as a powerful inducer of autophagy (Ogata et al, 2006;Yorimitsu et al, 2006). Recently we have shown that autophagy induced by hypericin-PDT in mouse embryonic fibroblasts under apoptosis-deficient conditions (for example, Bax/Bak double knockout) turns into a lethal pathway (Buytaert et al, 2006), possibly due to increased persistence in the absence of caspase signaling.…”
Section: Discussionmentioning
confidence: 54%
“…Intriguingly, parallel to UPR induction hypericin-PDT induces Atgs ( Table 1), suggesting that this cellular degradation process may be initiated to reestablish ER homeostasis following photodamage. This is supported by recent studies pointing to ER stress as a powerful inducer of autophagy (Ogata et al, 2006;Yorimitsu et al, 2006). Recently we have shown that autophagy induced by hypericin-PDT in mouse embryonic fibroblasts under apoptosis-deficient conditions (for example, Bax/Bak double knockout) turns into a lethal pathway (Buytaert et al, 2006), possibly due to increased persistence in the absence of caspase signaling.…”
Section: Discussionmentioning
confidence: 54%
“…39,40 In addition to participating in the ER stress-induced apoptosis, IRE1 has been shown to promote autophagy in the eukaryotic cells. 26 The kidneys in our untreated Imai rats showed a marked increase in IRE1 abundance, which was associated with marked elevation of ASK1, phosphorylated Representative Western blots and group data depicting the abundance of cytoplasmic (cNrf2) and nuclear (nNrf2) Nrf2, Akt, and P-Akt, in the untreated and ARB treated Imai groups. n 5 6 in each group.…”
Section: Discussionmentioning
confidence: 84%
“…ER stress has been shown to trigger autophagy in the kidney and other tissues. [26][27][28] In fact the observed activation of the ER stress-induced apoptotic pathway in 512 513 514 515 516 517 518 519 520 521 522 523 524 525 526 527 528 529 530 531 532 533 534 535 536 537 538 539 540 541 542 543 544 545 546 547 548 549 550 551 552 553 554 555 556 557 558 559 560 561 562 563 564 565 566 567 568 569 570 571 572 573 574 575 576 577 578 579 580 581 582 583 584 585 586 587 588 589 590 591 592 593 594the kidneys of our untreated Imai rats was accompanied by marked upregulation of LC3, which is a well-known marker of autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy selectively degrades aggregated proteins that accumulate in the ER lumen, such as the mutant secretory protein α1-antitrypsin 121 . Additionally, studies of yeast and mammalian cells demonstrate that autophagy mediates ER homeostasis by selectively segregating portions of this organelle network; this process has been termed ER-phagy or reticulophagy [122][123][124][125] . In addition to protein aggregates, selective autophagy is an important mechanism for the degradation of organelles.…”
Section: Box 1 | Autophagy and Protein Quality Controlmentioning
confidence: 99%